Voice dosimetry and monitoring, with emphasis on professional voice diseases: Critical review and framework for future research. (2nd April 2016) - Manfredi, Claudia; Dejonckere, Philippe H.
Abstract : Professional voice has become an important issue in the field of occupational health. Similarly, voice diseases related to occupations gain interest in insurance medicine, particularly within the frame of specific insurance systems for occupational diseases. Technological developments have made possible dosimetry of voice loading in the work-place, as well as long-term monitoring of relevant voice parameters during professional activities. A critical review is given, with focus on the specificity of occupational voice use and on the point of view of insurance medicine. Remaining questions and suggestions for future research are proposed.